THBS1 is a new autosomal recessive non-syndromic hearing impairment gene - Thashi Bharadwaj; Anushree Acharya; Fati Ullah Khan; Saadullah Khan; Irfan Ullah; Isabelle Schrauwen; Wasim Ahmad; Suzanne M. Leal (BMC Medical Genomics)
Abstract Background Prelingual hearing impairment (HI) is genetically highly heterogenous. Early diagnosis and intervention are essential for psychosocial development. In this study we investigated a consanguineous family from Pakistan with autosomal recessive (AR) non-syndromic sensorineural HI (NSHI). Methods A DNA sample from an HI member of a consanguineous Pakistani family segregating ARNSHL underwent exome sequencing. Using Sanger sequencing select variants were validated and tested for segregation using DNA samples from additional family members. We further investigated RNA expression data for the candidate gene in mouse and human inner ear and human inner ear organoids using data obtained from the gene Expression Analysis Resource. Results We identified thrombospondin 1 (THBS1) as a new NSHI gene. A homozygous frameshift variant [c.1470del: p.(Ile491Serfs*45)] was observed in the three hearing-impaired and in the heterozygous state in three unaffected family members. Unlike for most ARNSHI, hearing-impaired individuals had audiograms with a sloping pattern, showing more pronounced HI in the mid and high frequencies (ranging from moderate to profound) compared to the low frequencies. RNA expression data indicates THBS1 is expressed during human inner ear development. Additionally, THBS1 is expressed in the cochlear epithelium and supporting cells of the mouse inner ear during embryonic and postnatal stages. Previously, THBS1 was demonstrated to affect hearing in knockout mice by influencing the formation and function of afferent synapses in the inner ear. Conclusions Our findings highlight THBS1 as a potential novel candidate gene for human HI characterized by a sloping high-frequency audio profile. This discovery enhances our understanding of the genetic etiology of HI and will aid in advancing molecular diagnosis.